Effects of Different Watering Regimes on the Phytochemical Components and Physiological Parameters of Leaf Methanolic Extracts of Aloe Vera and Cassia Tora (Journal of Pure and Applied Sciences (Science Forum), 2025)
This study investigates the influence of varying watering regimes on the phytochemical composition and physiological responses of Aloe vera and Cassia tora leaf extracts prepared using methanol. The primary objective was to evaluate how different water stress levels affect the production of bioactive compounds and physiological parameters within these medicinal plants. Four distinct watering treatments were applied: daily watering (control), and extended intervals of 2, 4, and 8 days between watering cycles. Standard phytochemical and physiological assays were employed to detect and quantify the presence of key secondary metabolites, including alkaloids, flavonoids, tannins, saponins, phenolics, and terpenoids. Both qualitative and quantitative analyses were conducted to characterize the chemical profiles of the methanolic leaf extracts under each watering condition. The qualitative screening identified major phytochemical groups, while quantitative analysis measured their relative concentrations in response to water availability. Furthermore, Gas Chromatography-Mass Spectrometry (GC-MS) analysis was conducted to identify specific phytoconstituents present in the extracts of A. vera and C. tora. The findings reveal that water stress significantly influences both the concentration and diversity of phytochemicals in the plants studied, with potential implications for their medicinal efficacy and adaptive responses under drought conditions.